Book review: Vasudha Dalmia, Fiction as History: The Novel and the City in Modern North India. (January 2020) - Kumar, Prabhat
Vasudha Dalmia, Fiction as History: The Novel and the City in Modern North India, Ranikhet: Permanent Black, 2017, 428 pp.